NUANCES OF POSITIVIST HUMANISM IN CONTEMPORARY SOCIAL SCIENCES - Moraes Armesto, Leonardo; Roberto Alonso, Thabata (Journal of Interdisciplinary Debates, 2023)
The positioning of the social sciences guided by a logical positivist ideal is the motto of the approach and is built in a contemporary look, where the relations, event, bonds and conformations, are the product of a progressive dynamic that is done in a versatile way and far from a framed look fostered by predictability. Even though all this construction is supplemented by actions that seek to analyze all this mobilization, reality is reverberating and goes beyond premeditated standardization.